OPTIMALISASI AKREDITASI: EFEKTIVITAS SUPERVISI AKADEMIK MELALUI PEMBERDAYAAN GURU DAN PENERAPAN PEMBELAJARAN INOVATIF - Zulhijjah, Zulhijjah; Prasetyo, Muhammad Anggung Manumanoso (Jurnal Penjaminan Mutu, 2025)
This study aims to develop a model for the implementation of academic supervision to enhance teacher empowerment and its impact on the implementation of innovative learning. The research was conducted at Islamic Senior High School 4 East Aceh in Aceh Province. and employed a qualitative approach with descriptive survey techniques. The key informants included the head of the madrasah, the deputy head of the curriculum department, and several teachers. The findings indicate that the collaborative implementation of academic supervision through teacher empowerment significantly contributes to the development of innovative programs aimed at fostering effective learning. These elements collectively lead to a substantial improvement in the quality of education. Teacher empowerment emerges as a pivotal factor in advancing educational objectives. This research makes a significant contribution to the nuanced understanding of the intricate interplay between academic supervision, teacher empowerment, and innovative learning. The efficacy of academic supervision is demonstrated in the successful implementation of innovative learning at MAN 4 East Aceh. Despite challenges related to the availability of information technology, the madrasah is actively endeavoring to enhance its infrastructure and provide training to teachers for the seamless integration of technology into the learning process.